Survival in a burn injury of more than 80% TBSA – A case report. Issue 4 (October 2022) - Onah, Ifeanyichukwu I.; Mba, Uwakwe C.; Agbanusi, Onyeka I.; Okoli, Chinedu M.S.
Highlights: Survival of patients with more than 80% of the total surface area is rare in Nigeria. Poor nations lack adequate equipment and manpower to manage extensive burns. Initial resuscitation was with crystalloid and wound dressing was with silver dressing. Patient was commenced on high dose protein and calorie diets with high dose of vitamins. Commitment of the patient, his relations and the healthcare team is key to his survival. Abstract: The index patient was a 39 year old male who had more than 80 % TBSA burns and was managed at the Acute Burn Unit of the hospital. The aim is to outline the management and first ever recorded survival in the hospital of an adult patient who sustained burn injury of more than 80 % TBSA following cooking gas cylinder explosion while cooking in his kitchen. The study was retrospective. The history, physical examination, results of investigations and treatment were all gotten from the case file of the patient. The physical examination showed mixed superficial and deep dermal burn injuries (majorly superficial dermal thickness with patches of deep dermal) on head and neck (6 %), anterior trunk (17 %), posterior trunk (18 %), right upper limb (8 %), left upper limb (7 %), right lower limb (13 %), and left lower limb (12 %), making a total of 81 % with suspicion of inhalational injury. The Abbreviated Burn Severity Score was 12 making him have less than 10 % chance of survival. Patient was treated over a period of 32 days and was discharged home with complete re-epithelization of his wounds except for few raw areas. His vitals remained fairly stable while on admission except for occasional fever and raised white blood cell counts. He is continuing with follow up on outpatient basis.